2018
DOI: 10.1039/c8se00039e
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the identification of high-potential materials for cost-efficient membrane-based post-combustion CO2capture

Abstract: Identification of polymeric materials with a high potential to achieve significant cost-reductions for membrane-based CO2capture from a cement plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…Many other methods are also under development, including adsorption from flue gas, direct air capture, chemical looping, membrane separation, cryogenic separation, etc. The cost for amine scrubbing is around $37−121/tonCO2, [351][352][353] but by using membrane technologies, it has the potential to reduce to $25/tonCO2. 353,354 To achieve low carbon emission, electrolysis of water is the most common way in addition to direct eCO2RR.…”
Section: Economic Analysis Of Formic Acid Synthesis From Co2 41 Genmentioning
confidence: 99%
“…Many other methods are also under development, including adsorption from flue gas, direct air capture, chemical looping, membrane separation, cryogenic separation, etc. The cost for amine scrubbing is around $37−121/tonCO2, [351][352][353] but by using membrane technologies, it has the potential to reduce to $25/tonCO2. 353,354 To achieve low carbon emission, electrolysis of water is the most common way in addition to direct eCO2RR.…”
Section: Economic Analysis Of Formic Acid Synthesis From Co2 41 Genmentioning
confidence: 99%
“…The third capture chain, referred as chain C, considers the decarbonization of the WtE plant based on post-combustion CO 2 capture membranes. While membrane-based CO 2 capture from a flue gas with a CO 2 content around 10% has been shown be less competitive than solvent-based technologies at high CO 2 capture ratios, membranes with high performances have been shown to exhibit a stronger potential when partial capture is considered (Roussanaly et al, 2018). Here, an advanced membrane with a CO 2 /N 2 selectivity of 75 and a CO 2 permeance of 15 m 3 STP /(m 2 .h.bar) is considered.…”
Section: Co 2 Capture and Ccs Chain Optionsmentioning
confidence: 99%
“…A summary of the content of each module and their technical and cost basis is available in Jakobsen et al (2017). Details on the technical and cost basis of each of the modules of the iCCS tool can be found in previously published studies: post-combustion amine-based CO 2 capture (Husebye et al, 2012;Roussanaly et al, 2013a), post-combustion membrane-based CO 2 capture (Roussanaly et al, 2016(Roussanaly et al, , 2018, CO 2 transport via pipeline or ship (Roussanaly et al, 2013b, CO 2 storage in saline aquifer and EOR storage (Roussanaly and Grimstad, 2014). Key technical and cost aspects considered in the evaluation of each of the element of the WtE plant with the CCS chain are summarized in Table 2 in the context of the present study.…”
Section: Wte Plant and Ccs Value Chain Modelingmentioning
confidence: 99%
“…Ramasubramanian et al reported a CO 2 capture cost of $25/tonne CO 2 using an assumed membrane performance of CO 2 permeance of 3000 GPU (~8.2 m 3 (STP)/(m 2 h bar)) and CO 2 /N 2 selectivity of 140 [124]. More recently, membrane properties required for post-combustion carbon capture were systematically investigated [132,133], and a permeance of at least 3 m 3 (STP)/(m 2 h bar) with high selectivity should be achieved to be competitive to MEA absorption system. Even though the required high-performance membrane has not yet been achieved, their investigations emphasized quantitatively the need of improving the present membrane performance to realize a purely membrane-based process for CO 2 capture.…”
Section: Gas Separation Membrane Systemmentioning
confidence: 99%
“…Moreover, the CO 2 capture cost for membrane system is significantly dependent on the required CO 2 capture ratio. It is reported that membrane-based post-combustion CO 2 capture can benefit from lower CO 2 capture ratio with a 55% cost reduction [131], and CO 2 capture ratios lower than 90% would significantly improve the competitiveness of membrane-based carbon capture and lead to large cost reduction [132]. However, the overall benefit should be further investigated through the whole value chain.…”
Section: Gas Separation Membrane Systemmentioning
confidence: 99%